Tunneling nanotubes and tumor microtubes - emerging data on their roles in intercellular communication and pathophysiology: summary of an International FASEB Catalyst Conference October 2023 - Lou, Emil; Vérollet, Christel; Winkler, Frank; Zurzolo, Chiara; Valdebenito-Silva, Silvana; Eugenin, Eliseo (The FASEB journal, 2024)
In the past decade, there has been a steady rise in interest in studying novel cellular extensions and their potential roles in facilitating human diseases, including neurologic diseases, viral infectious diseases, cancer, and others. One of the exciting new aspects of this field is improved characterization and understanding of the functions and potential mechanisms of tunneling nanotubes (TNTs), which are actin-based filamentous protrusions that are structurally distinct from filopodia. TNTs form and connect cells at long distance and serve as direct conduits for intercellular communication in a wide range of cell types in vitro and in vivo. More researchers are entering this field and investigating the role of TNTs in mediating cancer cell invasion and drug resistance, cellular transfer of proteins, RNA or organelles, and intercellular spread of infectious agents, such as viruses, bacteria, and prions. Even further, the elucidation of highly functional membrane tubes called “tumor microtubes” (TMs) in incurable gliomas has further paved a new path for understanding how and why the tumor type is highly invasive at the cellular level and also resistant to standard therapies. Due to the wide-ranging and rapidly growing applicability of TNTs and TMs in pathophysiology across the spectrum of biology, it has become vital to bring researchers in the field together to discuss advances and the future of research in this important niche of protrusion biology.
Zuerst veröffentlicht: 11. März 2024
Gesehen am 02.08.2024